The use of bemiparin in obstetric antiphospholipid syndrome - N K Tetruashvili; T B Ionanidze; A A Agadzhanova; I V Menzhinskaya (IP Berlin A.V., 2015)
A study on the treatment of obstetric antiphospholipid syndrome in women with recurrent miscarriage by assigning low molecular weight heparin - bemiparin. The results show that the therapeutic effects of the drug as a preventive and therapeutic doses side effects are not registered. It was possible to achieve a full-term pregnancy to prolong life in 93.5% of cases, premature birth due to placental insufficiency observed in 6.5% of cases. None of the observation is marked by thrombocytopenia, bleeding in the second and third trimesters of pregnancy. At delivery blood loss did not exceed the standard indicators. Anticoagulation bemiparin based therapy was continued for 6 weeks of the postpartum period for the prevention of thrombotic complications.